2016
DOI: 10.1016/j.oraloncology.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Co-targeting ALK and EGFR parallel signaling in oral squamous cell carcinoma

Abstract: Squamous cell carcinoma (SCC) comprises 90% of all head and neck cancers and has a poor survival rate due to late-stage disease that is refractive to traditional therapies. Epidermal growth factor receptor (EGFR) is over-expressed in greater than 80% of head and neck SCC (HNSCC). However, EGFR targeted therapies yielded little to no efficacy in clinical trials. This study investigated the efficacy of co-targeting EGFR and the anaplastic lymphoma kinase (ALK) whose promoter is hypomethylated in late-stage oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
2
21
0
2
Order By: Relevance
“…Cell viability was determined using the Cell Titer 96 ® Aqueous Non‐Radioactive Cell Proliferation Assay (Promega, Madison, WI, USA) as described . Cells were plated and treated for 24 hours with serum‐free DMEM containing CPZ analogs at the indicated concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell viability was determined using the Cell Titer 96 ® Aqueous Non‐Radioactive Cell Proliferation Assay (Promega, Madison, WI, USA) as described . Cells were plated and treated for 24 hours with serum‐free DMEM containing CPZ analogs at the indicated concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were injected subcutaneously in the flank with 3 × 10 6 Cal‐27 cells as previously described . When tumors grew to 100 mm 3 , mice were stratified into five experimental groups (n = 5 per group) that received the following treatments via intra‐tumor injection every other day for four weeks: vehicle control (100 μL of 0.25% EtOH diluted in sterile saline), 120 μg of CPZ, CIDD‐24, CIDD‐99, or CIDD‐111 diluted in 100 μL sterile saline (final concentration of 0.25% EtOH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…regulating invasiveness and metastatic progression in HNSCC, 10 and ALK is upregulated in advanced disease compared to early-stage tumors. 11 A recent study reported that cotargeting ALK and EGFR using TAE684 and gefitinib significantly reduces HNSCC cell proliferation in vitro and decreases tumor volumes of a cell line derived xenografts by 30%. 11 However, whether the effectiveness of the combination of gefitinib and TAE684 was due to inhibition of EGFR and ALK was uncertain, since TAE684 has multiple targets other than ALK.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity was assessed using the Cell Titer 96 ® Aqueous Non‐Radioactive Cell Proliferation Assay (Promega, Madison, WI, USA) according to manufacturer's protocol. Cells were plated and treated for 48 hours with DMEM containing thymol at the indicated concentrations as previously described . Final DMSO concentrations were maintained at 0.1%.…”
Section: Methodsmentioning
confidence: 99%